Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3329/bjpt.v28i1.54205
|View full text |Cite
|
Sign up to set email alerts
|

New records of Euglenophyceae for Bangladesh

Abstract: A total of 8 species of Euglenophyceae where 5 species of Euglena namely, Euglena lucens Günther, E. paludosa Mainx., E. gaumei Allorge & Lefèvre , E. heimii Lef., E. mangini Lefévre, and 3 species of Lepocinclis namely, Lepocinclis ovum var. deflandriana (Ehrenberg) Lemmermann, L. ovum var. globulus ( Perty) Lemmermann and L. steinii Lemmermann from Sylhet Division which are all new records for Bangladesh. Bangladesh J. Plant Taxon. 28(1): 11-15, 2021 (June)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 99%